Multitarget quantitative PCR improves detection and predicts cultivability of the pathogen Burkholderia pseudomallei. - Göhler, A; Trung, T; Hopf, V; Kohler, C; Hartleib, J; Wuthiekanun, V; Peacock, S; Limmathurotsakul, D; Tuanyok, A; Steinmetz, I (American Society of Microbiology, 2017)
Burkholderia pseudomallei is present in the environment in many parts of the world and causes the often-fatal disease melioidosis. The sensitive detection and quantification of B. pseudomallei in the environment are a prerequisite for assessing the risk of infection. We recently reported the direct detection of B. pseudomallei in soil samples using a quantitative PCR (qPCR) targeting a single type three secretion system 1 (TTSS1) gene. Here, we extend the qPCR-based analysis of B. pseudomallei in soil by validating novel qPCR gene targets selected from a comparative genomic analysis. Two hundred soil samples from two rice paddies in northeast Thailand were evaluated, of which 47% (94/200) were B. pseudomallei culture positive. The TTSS1 qPCR and two novel qPCR assays that targeted open reading frames (ORFs) BPSS0087 and BPSS0745 exhibited detection rates of 76.5% (153/200), 34.5% (69/200), and 74.5% (150/200), respectively. The combination of TTSS1 and BPSS0745 qPCR increased the detection rate to 90% (180/200). Combining the results of the three qPCR assays and the BPSS1187 nested PCR previously published, all 200 samples were positive by at least one PCR assay. Samples positive by either TTSS1 (n = 153) or BPSS0745 (n = 150) qPCR were more likely to be direct-culture positive, with odds ratios of 4.0 (95% confidence interval [CI], 1.7 to 9.5; P < 0.001) and 9.0 (95% CI, 3.1 to 26.4; P < 0.001), respectively. High B. pseudomallei genome equivalents correlated with high CFU counts by culture. In conclusion, multitarget qPCR improved the B. pseudomallei detection rate in soil samples and predicted culture positivity. This approach has the potential for use as a sensitive environmental screening method for B. pseudomalleiIMPORTANCE The worldwide environmental distribution of the soil bacterium Burkholderia pseudomallei remains to be determined. So far, most environmental studies have relied on culture-based approaches to detect this pathogen. Since current culture methods are laborious, are time consuming, and have limited sensitivity, culture-independent and more sensitive methods are needed. In this study, we show that a B. pseudomallei-specific qPCR approach can detect significantly higher numbers of B. pseudomallei-positive soil samples from areas where it is endemic compared with that from culture. The use of multiple independent B. pseudomallei-specific qPCR targets further increased the detection rate of B. pseudomallei compared with that from single targets. Samples with a high molecular B. pseudomallei load were more likely to be culture positive. We conclude that our quantitative multitarget approach might be useful in defining areas where there is a risk of B. pseudomallei infections in different parts of the world.